AB0021 In Psoriatic Arthritis Synovial Tissue Harbors Expanded T-Cell Clones Which Are not Fully Represented in Synovial Fluid or Blood Samples. (10th June 2014) - Musters, A.; Doorenspleet, M.E.; Klarenbeek, P.L.; Esveldt, R.E.; Baeten, D.L.; Gerlag, D.M.; Tak, P.-P.; de Vries, N.
Abstract : Background: T-cells play a key role in psoriatic arthritis (PsA). Nevertheless, the distribution and exact role of these cells remains unclear. Here, we study whether expanded T-cell clones are present in synovial tissue (ST), and whether such clones are also detectable in peripheral blood (PB) and synovial fluid (SF). Methods: ST and SF from inflamed knees was sampled in 2 PsA patients together with paired PB samples. Using next generation sequencing T-cell clones were identified by their unique T-cell receptor β-chain sequence. Clones with a frequency of ≥0.5% were arbitrarily considered to be expanded. Results: ST and SF samples from the same joint shared many of the expanded clones (see Table 1 ). Ninety percent (median, range 71-100%) of the expanded clones in ST were retrieved in SF, 33% of these being expanded in both samples. ST clones accounted for 14% of the SF T-cell repertoire. In PB 83% of the expanded ST clones were retrieved, 17% being expanded in both samples. Analysis of both inflamed knees in patient 1 showed that 83% of the expanded ST clones in the left knee were retrieved in the right knee, 80% of these being expanded in both. Conclusions: In PsA synovial tissue harbors expanded T-cell clones, which are not fully represented in synovial fluid or blood samples. Preliminary analysis indicates that different joints contain identical expanded T cell clones. Our results suggest that in PsA comprehensive analysis of inflammation-related expanded clones best focuses on ST, rather than PB and SF. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4456